Renewing innovation systems in agriculture and food: How to go towards more sustainability? - Coudel, E.; Devautour, H.; Soulard, C.T.; Faure, G.; Hubert, B. (Wageningen University & Research, 2012)
The future of agriculture lies not only with food production, but also with such concerns as food quality, ecosystem services, inclusion of marginalised populations, rural regeneration and energy production. Yet which innovations will help in achieving these developments? What role can research and public policies play? This book considers social and institutional innovations, as well as technical options. It demonstrates that there is no single path towards sustainable development. Rather we must find ways to encourage the emergence and co-existence of different types of agriculture and food systems.